Improving Farmer Knowledge on the Use of Subsidized and NonSubsidized Fertilizers in Sukoanyar Village, Turi Subdistrict, Lamongan Regency: Peningkatan Pengetahuan Petani Terhadap Penggunaan Pupuk Subsidi dan Nonsubsidi di Desa Sukoanyar, Kecamatan Turi, Kabupaten Lamongan - Safrina Khalisah Intan Rahmadani; Regina Ayu Septia Adriafirna; Eva Noviana Maulanur Rohmah; Dita Atasa (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The spread of fake fertilizers in Lamongan Regency is increasing, so farmers must be selective in choosing and using fertilizers for their rice fields. The demonstration plot socialization activity aims to increase the knowledge of farmers in Sukoanyar Village regarding the procedure for using fertilizers with the right dosage and how to distinguish fake fertilizers from quality fertilizers. In addition, there is soil testing on farmers' rice fields to determine the condition of their soil so that they can determine the right dose of fertilizer. The target of the demonstration plot socialization activities of the MUT (Soil Test Car) Team were farmers in Sukoanyar Village, Turi District, Lamongan Regency. The final evaluation results showed that there was an increase in farmers' knowledge by 1.5 points from before the socialization activities.